2005
DOI: 10.1007/s00425-005-0133-8
|View full text |Cite
|
Sign up to set email alerts
|

A role for nickel in osmotic adjustment in drought-stressed plants of the nickel hyperaccumulator Stackhousia tryonii Bailey

Abstract: The hypothesis that hyperaccumulation of certain metals in plants may play a role in osmotic adjustment under water stress (drought) was tested in the context of nickel hyperaccumulator Stackhousia tryonii. Field-collected mature plants of S. tryonii, grown in native ultramafic soil, were pruned to soil level and the re-growth exposed to five levels of water stress (20, 40, 60, 80 and 100% field capacity; FC) for 20 weeks. Water stress had significant (P<0.05) influence on growth (biomass), water potential and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 20 publications
3
21
2
Order By: Relevance
“…Presumably, a decline in canola shoot biomass eventuated from suppressed cell expansion and cell growth arising from low turgor pressure (Mengel and Kirkby, 2001). The results are in contrast to the findings of Bhatia et al (2005) who stated that the growth of Stackhousia tryoni Bailey plant was adversely affected by FC conditions in a clay soil due to the poor porosity and root anaerobiosis.…”
Section: Shoot Dry Matter Yield (Sdmy)contrasting
confidence: 99%
See 2 more Smart Citations
“…Presumably, a decline in canola shoot biomass eventuated from suppressed cell expansion and cell growth arising from low turgor pressure (Mengel and Kirkby, 2001). The results are in contrast to the findings of Bhatia et al (2005) who stated that the growth of Stackhousia tryoni Bailey plant was adversely affected by FC conditions in a clay soil due to the poor porosity and root anaerobiosis.…”
Section: Shoot Dry Matter Yield (Sdmy)contrasting
confidence: 99%
“…6). The results were in agreement with the findings of Bhatia et al (2005), who observed a significant increase in SNC in drought-stressed S. tryonii plants. They suggested the positive osmoregulatory role in Ni.…”
Section: Nickel (Ni) Concentration and Content (1) Influence Of Nisupporting
confidence: 93%
See 1 more Smart Citation
“…The hyperaccumulation of certain metals may be important in the osmotic adjustment of plants under water stress, based on the discovery that the nickel (Ni) hyperaccumulation in Stackhousia tryonii is a trait protecting the plant from drought in serpentine soils, with Ni acting as an osmoregulatory agent (Bhatia et al 2005). Arsenic is closely related to the water consumption in hyperaccumulators.…”
Section: Discussionmentioning
confidence: 99%
“…whiting et al (2003) found no evidence that Ni or Zn can protect plants from polyethylene glycol (PeG)-induced osmotic stress. On the other hand, Bhatia et al (2005) reported that Ni may play a role in osmotic adjustment in the hyperaccumulator Stackhousia tryonii, thereby protecting it from drought stress. while not a hyperaccumulator, it is interesting to note that Yao et al (2012) found that Se treatment improved recovery of wheat seedlings from drought stress.…”
Section: Which Selection Pressures Favored the Evolution Of Hyperaccumentioning
confidence: 99%